Begin Again: A Biography of John Cage - Silverman, Kenneth (Evanston Northwestern University Press, 2010)
John Cage was a man of extraordinary and seemingly limitless talents: musician, inventor, composer, poet. He became a central figure of the avant-garde early in his life and remained at that pinnacle until his death in 1992 at the age of eighty. Now award-winning biographer Kenneth Silverman gives us the first comprehensive life of this remarkable artist. We follow Cage from his Los Angeles childhoodhis father was a successful inventorthrough his stay in Paris from 1930 to 1931, where immersion in the burgeoning new musical and artistic movements triggered an explosion of creativity in him and, after his return to the States, into his studies with the seminal modern composer Arnold Schoenberg. We see Cages early experiments with sound and percussion instruments, and watch as he develops his signature work with prepared piano, radio static, random noise, and silence. We learn of his many friendships over the years with other composers, artists, philosophers, and writers; of his early marriage and several lovers, both female and male; and of his long relationship with choreographer Merce Cunningham, with whom he would collaborate on radically unusual dances that continue to influence the worlds of both music and dance.Drawing on interviews with Cages contemporaries and friends and on the enormous archive of his letters and writings, and including photographs, facsimiles of musical scores, and Web links to illustrative sections of his compositions, Silverman gives us a biography of major significance: a revelatory portrait of one of the most important cultural figures of the twentieth century.
Keywords: Cage, John -- 1912-1992; 20th Century (1901-2000); Composer; Biography; Avant-garde; USA